Demoralisasi Sosial Peserta Didik Dalam Pendidikan: Industrialisasi Kurikulum Di Universitas Pada Era Digital - Zainal Abidin (Indonesian Journal of Social Science Education (IJSSE), 2023)
Industrialization has changed human perspective and morality. At the same time, government policies have encouraged students to become innovators. This policy has caused demoralization among Indonesian students in the Revolution 4.0 era. The research method used is descriptive using a qualitative approach, using observation, interviews, and formal and informal policy reviews available online. Objectively describes a university that has changed in response to government policies. Higher education processes have abandoned morality because they have industrialized and strived for innovation. Educational institutions cannot act independently because they are limited by the interests of the state. At the same time, it also fails to dynamically articulate the meaning of the digital revolution, which only focuses on products and workplaces. Criticism and reflection are needed to imbue students with decency and integrity. Such a constructive response is needed to curb the demoralization process that has occurred in the digital age.